Detention and denial the case for candor after Guantanamo - Wittes, Benjamin (Brookings Institution Press, 2011)
Discusses the legal, political, and moral ramifications of the current U.S. approach to handling detention of terrorist suspects and reviews in particular the historical and current uses of preventive detention under American law in arguing for a formal, statutory system of rules to govern detention in the context of counterterrorism operations.